(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the impact of natural and man-made emergency situations on human behavior, the peculiarities of spiritual and spiritual preparation in emergency situations, the concept of psychological preparation, its essence, the importance of emergency situations in preparing students to act in emergency situations features of impact, peculiarities of moral-psychological education of students in emergency situations are discussed.